2011
DOI: 10.1002/we.469
|View full text |Cite
|
Sign up to set email alerts
|

Optimal turbine spacing in fully developed wind farm boundary layers

Abstract: As wind farms become larger, the asymptotic limit of the ‘fully developed’, or ‘infinite’, wind farm has been receiving an increased interest. This limit is relevant for wind farms on flat terrain whose length exceeds the height of the atmospheric boundary layer by over an order of magnitude. Recent computational studies based on large eddy simulation have identified various mean velocity equilibrium layers and have led to parameterizations of the effective roughness height that allow the prediction of the win… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
233
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 306 publications
(242 citation statements)
references
References 19 publications
8
233
1
Order By: Relevance
“…10 and 11, where a thought experiment illustrated how considering only wind speeds and turbine specifications can yield generation rates that are physically unrealizable. The method is based on an analytical description of the momentum balance of the wind farm, a central concept used in similar studies on large-scale wind power limits (20)(21)(22) or for other forms of renewable energy such as tidal power (23,24) (detailed methodology is given in SI Appendix). It assumes that when wind farms extend tens of kilometers downwind, horizontal kinetic energy has either been extracted from the mean flow by the first few rows of turbines or has been lost to turbulent dissipation, so that the generation rate of wind turbines further downwind is then limited by the downward flux of kinetic energy.…”
Section: Methodsmentioning
confidence: 99%
“…10 and 11, where a thought experiment illustrated how considering only wind speeds and turbine specifications can yield generation rates that are physically unrealizable. The method is based on an analytical description of the momentum balance of the wind farm, a central concept used in similar studies on large-scale wind power limits (20)(21)(22) or for other forms of renewable energy such as tidal power (23,24) (detailed methodology is given in SI Appendix). It assumes that when wind farms extend tens of kilometers downwind, horizontal kinetic energy has either been extracted from the mean flow by the first few rows of turbines or has been lost to turbulent dissipation, so that the generation rate of wind turbines further downwind is then limited by the downward flux of kinetic energy.…”
Section: Methodsmentioning
confidence: 99%
“…For example, an optimization study utilizing Large Eddy Simulation (LES) has suggested the optimal spacing of HAWTs to be 15 D on the basis of minimizing costs per square rotor diameter. 4 More recently, a row-offset arrangement was demonstrated to allow for a greater wake recovery due to the increased streamwise spacing within the array. 5 Moreover, by decreasing the power output of upstream turbines, the performance of downstream turbines and the power output of the array as a whole can be increased.…”
Section: Introductionmentioning
confidence: 99%
“…Recent extensive application of the actuator disc model in the numerical simulation of wind farms can be found in the works of Meyers and Meneveau (2012) and Calaf et al (2010). El Kasmi and Masson (2008) developed a modified k-e model for the actuator disc accounting for energy exchange between large and small scale turbulence structures in the region close to the disc.…”
mentioning
confidence: 99%